Electronic Structure of Thiol-Capped CdTe Quantum Dots and CdTeQD–Carbon Nanotube Nanocomposites - Sarkar, Sunandan; Saha, Supriya; Pal, Sougata; Sarkar, Pranab (Journal of physical chemistry. C, 2012)
Thiol-capped CdTe quantum dots (QDs) have recently become the subject of intense investigation because of their diverse applications ranging from optoelectronic devices to the fabrication of solar cells. To achieve the desired functionalities, one must have clear understanding of the electronic structure of thiol-capped CdTe nanocrystals which is still lacking in the literature. In this paper, we have explored the electronic structure of relatively large thiol-capped CdTe QDs by taking advantage of the efficacy of the SCC–DFTB method. Our emphasis will be on the stability, charge transfer, density of states, and HOMO–LUMO gap of the dot as a function of both size and morphologies. We also studied the electronic structure of CdTeQD–carbon nanotube (CNT) nanocomposites. The effects of modulation of the band alignment through the variation in size of CdTe QDs on the electron injection rate from CdTe QD to CNT in CdTeQD–CNT nanohybrids have been explored.